2019
DOI: 10.1093/molbev/msz031
|View full text |Cite
|
Sign up to set email alerts
|

Neofunctionalization of Mitochondrial Proteins and Incorporation into Signaling Networks in Plants

Abstract: Because of their symbiotic origin, many mitochondrial proteins are well conserved across eukaryotic kingdoms. It is however less obvious how specific lineages have obtained novel nuclear-encoded mitochondrial proteins. Here, we report a case of mitochondrial neofunctionalization in plants. Phylogenetic analysis of genes containing the Domain of Unknown Function 295 (DUF295) revealed that the domain likely originated in Angiosperms. The C-terminal DUF295 domain is usually accompanied by an N-terminal F-box doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Strikingly, many defencerelated genes were highly induced, including pathogenesisrelated PR1, PR4, PDF1.2b and phytoalexin deficient PAD3. Also, many known target genes of ANAC017, including AOX1a, UGT74E2, At2g04050 and At2g41730 were highly induced, indicating that the mitochondrial retrograde signalling via ANAC017 was activated in the rps10 mutant [9,10,40]. A gene ontology analysis confirmed that among the up-regulated genes common to P2 and P3, those related to pathogen response, stress response, abscisic acid signalling and glucosinolate biosynthesis were overrepresented (electronic supplementary material, table S5).…”
Section: Resultsmentioning
confidence: 91%
“…Strikingly, many defencerelated genes were highly induced, including pathogenesisrelated PR1, PR4, PDF1.2b and phytoalexin deficient PAD3. Also, many known target genes of ANAC017, including AOX1a, UGT74E2, At2g04050 and At2g41730 were highly induced, indicating that the mitochondrial retrograde signalling via ANAC017 was activated in the rps10 mutant [9,10,40]. A gene ontology analysis confirmed that among the up-regulated genes common to P2 and P3, those related to pathogen response, stress response, abscisic acid signalling and glucosinolate biosynthesis were overrepresented (electronic supplementary material, table S5).…”
Section: Resultsmentioning
confidence: 91%
“…These data emphasize the strong similarity in the gene-expression profiles of rpoTmp plants that differ for developmental stages and growth conditions. Remarkably, among the common up DEGs, 20 genes encode mitochondrial localized proteins and at least nine genes are induced by mitochondrial dysfunction and transcriptionally regulated by mitochondrial retrograde signaling, as AT12CYS2 [11], NDB4 [11], five different DUF 295 organellar genes [35] and UPOX that is an hallmark of oxidative stress [37]. All these data pointed to the presence of a strong mitochondrial stress in rpoTmp plants and prompted us to explore the possibility that defects in mitochondrial respiration are at the origin of the observed skoto-morphogenetic alteration.…”
Section: The Triple-response-like Phenotype Is Dependent On An Activementioning
confidence: 99%
“…In addition to its role in BIN2 degradation, the Kelch repeat-mediated KIB1-BIN2 interaction blocked the BIN2-BZR1 binding, thus further reducing the BIN2 phosphorylation activity [ 28 ]. It remains to be determined whether proteasome-mediated degradation is an evolutionally conserved mechanism in other plant species to regulate the phosphorylation activity of BIN2 homologs given a recent discovery of restricted distribution of KIB1 and its homologs in the Brassicaceae family and their extremely low expression in vegetative tissues [ 210 ]. It is interesting to note that the proteasome-mediated GSK3 degradation was previously shown to be induced by glucocorticoid in mammalian cells although the identity of a GSK3-interacting E3 ubiquitin ligase remains unknown [ 211 ].…”
Section: Bin2 the Negative Regulatormentioning
confidence: 99%